Nutrient responding peptide hormone CCHamide-2 consolidates appetitive memory - Yamagata, Nobuhiro; Imanishi, Yasuhito; Wu, Hongyang; Kondo, Shu; Sano, Hiroko; Tanimoto, Hiromu (Frontiers in Behavioral Neuroscience, 2022)
CCHamide-2 (CCHa2) is a protostome excitatory peptide ortholog known for various arthropod species. In fruit flies, CCHa2 plays a crucial role in the endocrine system, allowing peripheral tissue to communicate with the central nervous system to ensure proper development and the maintenance of energy homeostasis. Since the formation of odor-sugar associative long-term memory depends on the nutrient status in an animal, CCHa2 may play an essential role in linking memory and metabolic systems. Here we show that CCHa2 signals are important for consolidating appetitive memory by acting on the rewarding dopamine neurons. Genetic disruption of CCHa2 using mutant strains abolished appetitive long-term memory (LTM) but not short-term memory (STM). A post-learning thermal suppression of CCHa2 expressing cells impaired LTM. In contrast, a post-learning thermal activation of CCHa2 cells stabilized STM induced by non-nutritious sugar into LTM. The receptor of CCHa2, CCHa2-R, was expressed in a subset of dopamine neurons that mediate reward for LTM. In accordance, the receptor expression in these dopamine neurons was required for LTM specifically. We thus concluded that CCHa2 conveys a sugar nutrient signal to the dopamine neurons for memory consolidation. Our finding establishes a direct interplay between brain reward and the putative endocrine system for long-term energy homeostasis.